Pokemon. BW rival destinies. Set 2 [videorecording (DVD)]. ([Publisher not identified], 2014)
Ash is rarin' to battle Gym Leader Clay in Driftveil City! Then the friends witness a dramatic Pokemon trade and evolution. But the excitement has just begun. Professor Juniper invites Ash and his pals to join him in what he promises will be a thrilling adventure₇and he keeps his promise! In Mistralton City, Ash discovers a Gym Leader with an unusual battle style. And get ready for some explosive action when our heroes prepare to participate in the Clubsplosion Tournament!